2023
DOI: 10.1111/padr.12591
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in a Pandemic: Evidence from California

Jenna Nobles,
Alison Gemmill,
Sungsik Hwang
et al.

Abstract: The COVID‐19 pandemic was accompanied by social and economic changes previously associated with fertility delay and reduction, sparking widespread discussion of a “baby bust” in the United States. We examine fertility trends using restricted vital statistics data from California, a diverse population of 40 million, contributing 12 percent of U.S. births. Using time series models that account for longer‐run fertility trends, we observe modest, short‐term reductions in births from mid‐2020 through early 2021. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…An early working paper by Wilde, Chen, and Lohmann (2020) (revised in this supplement as Wilde et al 2024) predicted that pandemic effects would be more acutely felt among more vulnerable populations in the United States, such as those of lower socioeconomic status (SES) or in states with higher COVID-19 mortality. However, according to Nobles et al (2023) and Bailey, Currie, and Schwandt (2023), the exact opposite occurred: birth declines were more acutely experienced among high-SES women in the early months of the pandemic, although this changed later in 2021 and 2022. Interestingly, similarly heterogeneous conclusions were drawn in Norway, where increases in birth rates were concentrated among women of prime childbearing ages (28-35), women who already had children, and those who had university degrees (Lappegård et al 2023).…”
Section: Fertility Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early working paper by Wilde, Chen, and Lohmann (2020) (revised in this supplement as Wilde et al 2024) predicted that pandemic effects would be more acutely felt among more vulnerable populations in the United States, such as those of lower socioeconomic status (SES) or in states with higher COVID-19 mortality. However, according to Nobles et al (2023) and Bailey, Currie, and Schwandt (2023), the exact opposite occurred: birth declines were more acutely experienced among high-SES women in the early months of the pandemic, although this changed later in 2021 and 2022. Interestingly, similarly heterogeneous conclusions were drawn in Norway, where increases in birth rates were concentrated among women of prime childbearing ages (28-35), women who already had children, and those who had university degrees (Lappegård et al 2023).…”
Section: Fertility Dynamicsmentioning
confidence: 99%
“…Later, even in countries which did experience nominal declines, the underlying mechanisms behind the changes became clearer and the causal effects of the pandemic became increasingly suspect. For example, in the United States, the single-digit declines in birthrates were shown to be almost solely concentrated among foreign-born individuals, leading to concerns that the declines were an artifact of changing denominators rather than numerators (Bailey, Currie, and Schwandt 2023;Nobles et al 2023). These studies-once accounting for time trends and characteristics of the native-born mothers-showed virtually no pandemic effects at all-except for increases in birth rates later in 2021.…”
Section: Fertility Dynamicsmentioning
confidence: 99%